Variety between regions legal systems, danger of disintegration and question about future of the Union /A philosophical study about effect of Variety between legal systems on unity and disintegration - Hussein, Ismail Namiq; Latif, Shilan Raouf (Journal of Legal and Political Studies, 2025)
In this research, we followed an analytical and comparative method, to study and discuss the right of the regions in the federal state to have legal system, and then we dealt with the effect of the variation between the legal systems of the regions on the future of the union. we concluded that one or more regions in the federal state may have a different legal system, this variation may be explicitly like province of Quebec in Canada, and Louisiana state in USA, or may be implicitly like South Africa, which followed a hybrid legal system. this variety between legal systems of the federal state doesn’t threat on the future of the Union, but if it is not properly handled, then the Union will be faced to danger of disintegration and abolition. In order to ensure the success of federalism in Iraq, we have proposed that a mixed legal system will be adopted in Iraq, both at the federal and regions levels, and that each region will be given the right to choose its legal system and to choose how to regulate legal relations within the borders of the region, with binding by bases, principals and purposes of the Union. Keywords: purpose of law, conflict, proximity, shariaah, sources of law.
Keywords: Keywords purpose of law; conflict; proximity; shariaah; sources of law